Emergency Management of Cyanide Toxicity: An Evidence-Based Reference for Healthcare Assistants, Paramedics, and Health Informatics Professionals An Updated Review - Alqahtani, Ayidh Jafar Ayidh; Ghawanni, Sereen Saeed; Alqahtany, Musfir Muteb Saad; Alqahtani, Sultan Saif; Al-Dossari, Saleh Salem; Almutairi, Raud Mater H.; Albaqami, Mohammed Faisal B.; Alqahtani, Ali Moeed; Alsowaigh, Saad Mohammed Saad; Alsulami, Salem Eid Ayad (International Journal of Aquatic Research and Environmental Studies, 2025)
Background: Cyanide toxicity is a rare but rapidly fatal medical emergency that results from inhibition of mitochondrial oxidative phosphorylation, leading to cellular hypoxia despite adequate oxygen delivery. Exposure occurs through inhalation of hydrogen cyanide gas, ingestion of cyanide salts or cyanogenic foods, occupational accidents, structural fires, and certain pharmaceutical agents. Owing to its nonspecific clinical presentation and rapid progression, early recognition and prompt treatment are essential for reducing morbidity and mortality. Aim: This review aims to provide a comprehensive overview of cyanide toxicity, including its epidemiology, etiology, pathophysiology, clinical manifestations, diagnostic evaluation, emergency management, prognosis, and complications, with emphasis on evidence-based practices relevant to emergency medicine, healthcare assistants, paramedics, and health informatics professionals. Methods: A narrative literature review was conducted using current peer-reviewed studies, toxicology references, and clinical guidelines addressing cyanide poisoning, its underlying mechanisms, diagnostic approaches, antidotal therapy, and supportive management. Results: Cyanide poisoning primarily disrupts aerobic cellular respiration through inhibition of cytochrome c oxidase, resulting in histotoxic hypoxia, profound lactic acidosis, and multiorgan dysfunction. Diagnosis remains predominantly clinical, supported by elevated serum lactate, metabolic acidosis, and characteristic exposure history. Immediate stabilization, decontamination when indicated, and early administration of hydroxocobalamin constitute the cornerstone of treatment. Delayed intervention significantly increases mortality and the risk of persistent neurological sequelae, including Parkinsonian syndromes. Conclusion: Cyanide toxicity remains a time-critical emergency requiring rapid clinical recognition and immediate intervention. Early diagnosis, multidisciplinary management, and prompt antidotal therapy substantially improve survival and neurological outcomes. Ongoing education of frontline healthcare professionals and adherence to evidence-based emergency protocols are essential to optimize patient care and minimize the devastating consequences of cyanide poisoning.
Keywords: Cyanide toxicity; Cyanide poisoning; Hydrogen cyanide; Histotoxic hypoxia; Cytochrome c oxidase; Hydroxocobalamin; Sodium thiosulfate; Emergency medicine; Toxicology; Smoke inhalation; Metabolic acidosis; Antidote.